Improving MSME Business by Preparing Financial Reports Based on MSME SAK - Nasihin, Ihsan; Purwandari, Dian; Lasmini, Lilis; Ardiansyah, Hendri Nur (Jurnal PKM: Pengabdian Kepada Masyarakat, 2025)
The purpose of this community service is to help MSMEs record simple financial transactions and prepare financial reports based on the MSME SAK which are used by MSMEs fostered by Pojok Entrepreneur as a basis for decision making. The community service method used is the training and mentoring method. The training method is used by presenting material on the importance of preparing financial reports and simulations and discussions in making and preparing financial reports based on MSME SAK which are taken from the financial transactions of MSMEs. Meanwhile, the mentoring method is carried out by creating a WhatsApp group and conducting routine monitoring to evaluate the preparation of financial reports that have been carried out. The results of the community service that have been carried out are that there are still many MSMEs fostered by Pojok Entrepreneur who have not recorded daily financial transactions and stored proof of transactions, so that MSMEs still have difficulty in preparing financial reports. However, with this community service, MSMEs fostered by Pojok Entrepreneur have begun to prepare simple financial reports that can be used as a reference in decision making